PEMAHAMAN MASYARAKAT TERHADAP JUAL BELI MUKHADHARAH DALAM PERSPEKTIF EKONOMI ISLAM (Studi Kasus Di Kecamatan Kuta Makmur Kabupaten Aceh Utara) - fuadi fuadi (IAIN Langsa, 2021)
This study aims to determine the public’s understanding of the implementation of Mukhadharah purchasing and selling from the Islamic economic perspective in the Kuta Makmur subdistrict. This study used a qualitative approach. The results showed that the community’s understanding of the contract made by both parties that occurred before the harvest period was considered valid and fulfilled the elements of the agreement. In purchasing and selling on trees not fully based on the pillars and the legal terms of sale and purchase and contrary to the provisions of Syara’ because they contain Gharar elements and in the execution of taking the goods there are irregularities so that the sale and purchase were not valid because the quality and quantity of goods were different after purchase. So, it concluded that the sale and purhase of Mukhadharah in the Kuta Makmur subdistrict were illegal.